Repetition of the Marriage Contract (Shihhah) in the Rifaiyah’s Tradition - Muftadin, Dahrul (Jurnal Hukum Islam, 2021)
In the tradition of Jama'ah Rifaiyah there is the practice of repeating the marriage contract called Shihhah. This tradition emerged from the understanding of the central figure of the Rifaiyah congregation, Kiai Ahmad Rifai, who categorized some Muslims who supported the Dutch colonial government into the category of wicked believers, including the Penghulu (Chieftain). Penghulu who are under the auspices of the colonial government are considered no longer have a "adil/fair" nature. This has resulted in any marriage process led by the government head being considered invalid, because the chieftain is not a fair believer who is required to lead the marriage process. This tradition lasted until the post-independence period. The purpose of this study is to find out the practice of shihhah from the colonial period until now and what factors are behind it. Field research with a descriptive-analytical approach found that the practice of shihhah among the Rifaiyah congregation experienced a shift. The practice of shihhah is still carried out by some Rifaiyah congregations even though the Indonesian government is no longer a colonial government. Some Rifaiyah congregations still practice shihhah on the grounds of a clash with a religious figure. However, many Rifaiyah congregations no longer practice shihhah.